Organic materials as saturable absorber for pulse generation at telecommunication window / Sameer Salam M.H. Mohammed Hussein - Sameer Salam M.H. , Mohammed Hussein (2020)
This thesis demonstrates several types of fiber lasers based on newly developed organic materials as saturable absorbers (SAs). We used these SAs in all-fiber based erbium-doped fiber laser (EDFL) ring cavity to produce Q-switched and mode-locked pulses at telecommunication window, at ~ 1560 nm. Three different organic materials were used in this thesis: Bis[2-(4,6-difluorophenyl)pyridinato-C2 ,N](picolinato)iridium(III) (FIrpic), bis(8-hydroxyquinoline)zinc (Znq2) and Tris(8-hydroxyquinoline)aluminum (Alq3). Finding new materials is still one of the defining characteristics of nonlinear optics field, as the rapid development of SAs has provided several new opportunities for nonlinear optics. Throughout this work, organic material showed a very interesting performance in terms of pulse duration, pulse energy, damage threshold, stability, spectral tunability, nonlinear response and proved to have a great potential in fiber laser technology. Organic materials are bio-compatible, environment-friendly, light-weight and mechanically flexible. The SA thin-films based on FIrpic, Znq2 and Alq3 in conjunction with polyvinyl alcohol (PVA) were successfully fabricated, in a simple, straight and low-cost process. A small piece of fabricated SA thin-film was inserted between two ferrules to form SA device. A set of measurements were taken to characterize the fabricated SAs, such as Fourier transform infrared (FTIR) spectrometer, optical absorption, linear and non-linear transmission. Different kinds of Q-switched fiber lasers with very high stability were successfully demonstrated using these materials. At first, FIrpic was used to develop a Q-switched laser with single- and dual-wavelength operation. Then, Znq2 was used to demonstrate Qswitching pulsing with fixed and tunable wavelength operation. The produced pulse width was decreased from 6.6 µs to 2.8 µs, while the repetition rate was increased from 45 kHz to 85 kHz. Finally, Alq3 was used as a Q-switcher to produce pulses at 1.5 µm and 1.0 µm regions. At 1.5 µm region, the pulse width and repetition rate were tunable within 1.2 µs to 6.65 µs and 31.65 kHz to 144.5 kHz, respectively. At 1 µm region, Alq3 produced high pulse energy and high peak power of 0.8 μJ and 237.62 mW, respectively, in two different setups. Stable ultrafast soliton laser operations were also achieved by using the developed SAs. At first, FIrpic was used to demonstrate a mode-locked laser with pulse width and repetition rate of 120 ns and 3.43 MHz, respectively. Similarly, Znq2 was also successful as a mode-locker, where it was used to produce a laser with a pulse width of 1.46 ps and a repetition rate of 3.5 MHz. Finally, a pulse width of 820 fs and a repetition rate of 4.9 MHz was achieved by using Alq3. Alq3 produced mode-locking operation with single and multi-wavelength operation at 1.0 µm with pulse width and repetition rate of 5.96 ps and 6.84 MHz, respectively. In conclusion, this work has successfully drawn attention to the potentials that organic materials have in fiber laser technology especially for Q-switching and mode-locking applications.